2020
DOI: 10.3390/en13153993
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Soot Particle Number, Mass and Size Distribution along the Exhaust Line of a Heavy-Duty Engine Fueled with Compressed Natural Gas

Abstract: An experimental study has been conducted to provide a characterization of the transformations that particle size distributions and the number density of soot particles can encounter along the exhaust line of a modern EURO VI compliant heavy-duty engine, fueled with compressed natural gas. Being aware of the particles history in the exhausts can be of utmost importance to understand soot formation and oxidation dynamics, so that, new strategies for further reducing these emissions can be formulated and present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Instruments that provide real-time size distributions are the electrical low-pressure Atmosphere 2022, 13, 1675 2 of 20 impactor (ELPI) (Dekati Ltd., Kangasala, Finland) [17], the differential mobility sizer (DMS) (DMS500, Cambustion Ltd., Cambridge, UK) [18], and the engine exhaust particle sizer (EEPS) (model 3090, TSI Inc., Shoreview, MN, USA) [19]. Vehicle or aircraft exhaust, indoor or outdoor ambient air, or workplace environment measurements with such instruments are very common [20][21][22][23]. Many studies, however, raised concerns regarding the accuracy of such instruments measuring aerosol with not-well-defined properties, such as from vehicles or ambient air [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Instruments that provide real-time size distributions are the electrical low-pressure Atmosphere 2022, 13, 1675 2 of 20 impactor (ELPI) (Dekati Ltd., Kangasala, Finland) [17], the differential mobility sizer (DMS) (DMS500, Cambustion Ltd., Cambridge, UK) [18], and the engine exhaust particle sizer (EEPS) (model 3090, TSI Inc., Shoreview, MN, USA) [19]. Vehicle or aircraft exhaust, indoor or outdoor ambient air, or workplace environment measurements with such instruments are very common [20][21][22][23]. Many studies, however, raised concerns regarding the accuracy of such instruments measuring aerosol with not-well-defined properties, such as from vehicles or ambient air [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is based on conditions where adequate temperature and residence time enable the conversion efficiency of the TWC to surpass 90% for all targeted gaseous pollutants, facilitating soot and organic particles oxidation [32]. However, some investigations indicate an increase in PN downstream of the TWC, associating it with the formation of nucleation particles from UHC, CO and lubricating oil residues when the TWC does not present high conversion efficiencies of these species [24]. Furthermore, variations in PSD may result from diverse phenomena, some of which are opposing in nature.…”
Section: Steady-state Conditionsmentioning
confidence: 99%
“…Several studies have been focused on study ATS on PN emissions. Ditaso et al [24] investigated the changes in soot PN, mass, and Particle Size Distribution (PSD) throughout the exhaust line of a HD engine powered by CNG. Their investigation revealed that PN varies along the exhaust line, influenced by exhaust properties such as temperature and composition, as well as the presence of ATS devices.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles were linked to sulphur-driven nucleation of new particles in cooling dilution of the exhaust [ 252 ]. For all the fuels, non-volatile nanoparticles in sub-10 nm particle sizes were observed during engine braking, and they were most likely formed from lubricant-oil-originated compounds [ 253 ]. With all the fuels, the measured particulate and NOx emissions were significantly higher during the WLTC cycle compared to the NEDC cycle.…”
Section: Mitigation Measures For Road Traffic Pm Emissions and Its Im...mentioning
confidence: 99%